2021
DOI: 10.1108/par-09-2020-0138
|View full text |Cite
|
Sign up to set email alerts
|

Australian market response to COVID-19 as moderated by social media

Abstract: Purpose Emerging as a black swan event that stifled the global economy, COVID-19 is the first social media (SM) pandemic. In an unsocial age due to social distancing, SM relevance is intuitively magnified during a pandemic. This study aims to investigate the direct and moderating impact of Twitter on the Australian stock market during the COVID-19 info-pandemic. Design/methodology/approach As a natural experiment, a time-series regression measures the effect of the COVID-19 virus, proxied by the active cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the early stages of the COVID-19 outbreak, Lazzini et al (2022) found a significant Granger causality relationship between tweets on a given day and the FTSE MIB closing price. For the Australian stock market, Maia et al (2021) proved that when analysing market returns and estimating their volatility, a sentiment reflected in topic-related Tweets exerts a crucial role. Based on a sample covering 2000 firms listed on the NASDAQ and daily cumulative Twitter postings on COVID-19, Guan et al (2022) revealed that the majority of digitally evolved industries are resilient to adverse market sentiments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stages of the COVID-19 outbreak, Lazzini et al (2022) found a significant Granger causality relationship between tweets on a given day and the FTSE MIB closing price. For the Australian stock market, Maia et al (2021) proved that when analysing market returns and estimating their volatility, a sentiment reflected in topic-related Tweets exerts a crucial role. Based on a sample covering 2000 firms listed on the NASDAQ and daily cumulative Twitter postings on COVID-19, Guan et al (2022) revealed that the majority of digitally evolved industries are resilient to adverse market sentiments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different from earlier literature that explored single markets such as the United States (Chatterjee & French, 2022;Dey et al, 2022;Hasan, 2022;Khoury & Alshater, 2022;Subramaniam & Chakraborty, 2021;, China (Gong et al, 2022;Liu et al, 2021;Mezghani et al, 2021;Soltani & Abbes, 2022;Q. Wang & Liu, 2022;Xie et al, 2021), Australia (Maia et al, 2021;Tiwari et al, 2022), Italy (Lazzini et al, 2022;Niu et al, 2021), India (Debata et al, 2021;Sing & Singh, 2023), Saudi Arabia (Wasiuzzaman, 2022), the current study explores several leading equity markets. Additionally, the period was extended to cover the "fear" period, over which the markets were widely affected, and the "hope" period, over which the pharmaceutical companies strived to develop vaccines and remedies for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…While the COVID-19 pandemic is an unfortunate event, it offers a unique natural setting for capital market researchers to investigate the impact of this pandemic on firms’ performance and behaviour as well as the stock market’s performance. During the time of the COVID-19 pandemic, research has focused on the global macroeconomic impacts and firms’ market performance and disclosure behaviour (Baek et al , 2020; Choi, 2020; Chong and Momin, 2021; Cookson et al , 2020; Cui et al , 2021; Gormsen and Koijen, 2020; Huang and Ye, 2020; Larcker et al , 2020; Loughran and McDonald, 2023; Maia et al , 2021; McKibbin and Fernando, 2020; Mirza et al , 2020; Naeem et al , 2021; Ozili and Arun, 2020; Salisu and Vo, 2020; Xu et al , 2021; Wang and Xing, 2020; Yan et al , 2020; Yilmazkuday, 2020). For example, McKibbin and Fernando (2020) and Ozili and Arun (2020) discussed the global impact of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%